Agile Governance for Achieving Corruption-Free Areas: Case Study on Digital-Based Services at Padangan Hospital - Melvi Noviza; Ana Kumalasari; Cahya Lukito; Husny Gibreel Musa Saleh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The increase in corruption cases in the health sector not only disrupts the effectiveness of national health programs but also threatens the continuity and quality of healthcare services for the community. Good and rapid governance is needed, namely Agile Governance. The objective of this research is to provide strategic recommendations for the development of a more effective and efficient governance system in the hospital environment, as well as to enhance public trust in the healthcare services provided. This research is motivated by the importance of digital-based healthcare services in enhancing efficiency and transparency in the public sector, as well as reducing the potential for deviations and corruption. RSUD Padangan has received recognition for its implementation of risk management and cultural competence, making it a model hospital in the application of digital-based services. The method used in this research is qualitative with a case study approach according to Creswell (2015). Data collection was conducted using primary and secondary data. The main focus of this research is to analyze how the implementation of agile governance can enhance transparency and accountability in public services, as well as reduce the potential for corruption in the health sector. The research results show that the implementation of agile governance principles by RSUD Padangan successfully increased patient satisfaction and strengthened public trust in healthcare services. The implementation of digital services, cooperation with local government, and readiness to face emergency situations are key to achieving a corruption-free region status.